The susceptible-infected-recovered (SIR) based model for the spreading of information during electoral campaign via twitter / Noor Syamsiah Mohd Noor - Mohd Noor, Noor Syamsiah (Faculty of Computer and Mathematical Sciences, 2019)
Twitter has been prominently used among people especially during the electoral campaigns. Twitter helps the politicians to spread and share their political agenda as well as it helps citizens to communicate with them directly. This study aims to investigate the dynamics of information during electoral campaigns through Twitter from the mathematical point of view. This study employed an epidemiological model which is a system of differential equations known as Susceptible-Infected-Recovered (SIR) to describe how information spreads on Twitter during Malaysia’s 14th General Election. The model involves three state variables, which are active Twitter users (S), transmission node (I) and immune Twitter users (R). The data related to Malaysia’s 14th General Election which is before and after the election. The political parties and politicians as well as several popular tweets that turn out to be the trending topics during the electoral campaign have been collected. The influence of contact rate between active Twitter users and the transmission node as well as the influence of carrying capacity of the Twitter network on Malaysia’s 14th General Election was also analyzed. The results showed that the contact rate between active Twitter users and the transmission node as well as the carrying capacity of the Twitter network has significant influence in the electoral campaign.